Outbreaks of animosity against the West in China: effects on local brand consumption. Issue 4 (10th July 2017) - Heinberg, Martin
Abstract : Purpose: Local brands in emerging markets suffer from fierce competition and chronic disadvantages. The purpose of this paper is to investigate if outbreaks of animosity against the West (AAW) might benefit local brands by raising consumers' willingness to pay (WTP) and willingness to buy (WTB). Design/methodology/approach: The study employed 2 methods: structural equation modeling ( n =244 Chinese students); and experiment, multiple regression ( n =676 Chinese students, different sample than those included in study 1). Findings: AAW is different from ethnocentrism and the measurement has good validity and reliability. After an outbreak of animosity, AAW increases Chinese consumers' WTB local products. The WTP is also enhanced by AAW in such a situation. Under "normal" circumstances, there is no effect of AAW on the WTP. This might be due to the cost of substituting western goods for local ones (e.g. inferior perceived quality and other-signaling value). An outbreak of animosity presents a risk to consumers and thus lowers their overall WTP. Originality/value: The study introduces the construct "AAW, " which stretches the animosity construct to an inter-regional level. On such a level, it is possible to find consequences of animosity on local brand consumption, which have not been the focus of previous studies. Additionally, this research introduces the concept of WTP to animosity research. The measurement is built on a real economic exchange and better represents the cost aspects of substituting one brand for another.